Parental education and the WHO neonatal G-6-PD screening program: a quarter century later. - Kaplan, M; Hammerman, C; Bhutani, V K (Journal of Perinatology, 2015)
Neonatal screening for glucose-6-phosphate dehydrogenase (G-6-PD) deficiency in any population with a male frequency >3-5%, combined with parental education regarding the dietary, environmental and sepsis-related triggers for hemolysis was recommended by the WHO (World Health Organization) Working Group in 1989. As the aim of identifying G-6-PD deficiency in the newborn period is to avert or detect extreme hyperbilirubinemia developing at home, before the development of kernicterus, the parental role in identifying evolving icterus was considered integral to any screening program. Now, a quarter century after publication of this report, severe bilirubin neurotoxicity associated with G-6-PD deficiency continues to be encountered worldwide. Screening programs have not been universally introduced but several national or regional maternal child health programs have implemented neonatal G-6-PD screening. Some reports detail the role of parental education, based on the above mentioned principles, through a variety of audio-visual materials. The paucity of randomized controlled trials or validated evidence to demonstrate the effectiveness of the contribution of parental education fails to meet the ideal testable evidence-based approach. However, our review of the cumulative experience and evidence currently available does supply certain information reflecting a positive impact of screening programs combined with parental input. We propose that the current information is sufficient to continue to support and apply the Working Group's recommendations. In order not to waste unnecessary time available, data may be used in lieu of randomized trials to continue to recommend screening programs, as suggested, in high-risk regions. If the incidence of kernicterus associated with G-6-PD deficiency is to be diminished, G-6-PD screening in combination with parental explanation may be one instance in which the consensus approach suggested by the WHO Working Group, rather than reliance on (nonexistent) evidence-based studies, should continue to be practiced.